How do policy incentives influence the adoption of electric vehicles? - Ivanova, Elitza Vladimirova (2018)
Battery electric vehicles (BEVs) are an effective way to reduce fossil fuel consumption and greenhouse gas emissions. BEVs result in lower energy consumption, greenhouse gas emissions, and urban air pollution compared to internal combustion engine vehicles (ICEVs). Although the uptake of EVs has been significant in a short period of time, most government goals for adoption have not been met and the number of BEVs on the road is still low. Therefore, in order to reduce current greenhouse gas emissions from the transport sector, a vast number of governments have implemented different policy incentives, aiming to stimulate the mass adoption of electric vehicles. The policy makers have introduced two main types of policies – purchase-based and use-based. This work seeks to determine the relationship of those policy incentives to the market deployment of BEVs to mainstream consumers with demographics and vehicle attribute preferences most common to today’s new vehicle purchasers. Moreover, this research argues that policies intending to stimulate the uptake of BEVs should not focus on mainstream consumers, but instead they should refocus on niche markets and early adopters, targeting them differently. Regarding to that, this work also presents findings, that that there are two main groups of early adopters – high-end and low-end adopters, which have different socio-economic profile and different opinions of their vehicles with high-end adopters viewing their BEVs more preferentially. BEV policies approaching early adopters and niche markets differently would create complementary system that will lead to increased BEV market penetration and realization of intended societal benefits.